The 3Rs - Reflect, Review, Restructure - Waisman, Jackie (Operating Room Nurses Association of Canada Journal, 1995)
Greetings on behalf of the ORNAC Executive and Board. In this issue of the Journal I have the pleasure of sharing with you, the membership of ORNAC, some recent changes to the organizational structure of your association.